Effect of Staining Solutions and Repolishing on Composite Resin Color Change - Elham Zajkani; Maryam Abdoh Tabrizi; Amir Ghasemi; Hasan Torabzade; Mohammad Kharazifard (Islamic Dental Association of Iran, 2013)
Background and Aim : Success of composite restorations mainly depends on their color stability when in service. The present study aimed at assessing the effect of staining solutions and repolishing on composite resin color change .   Materials and Methods : In this experimental study, 200 specimens were fabricated with A2 and B2 shades of Spectrum (TPH, Dentsply) and Point 4 (Kerr, USA) composite resins (100 specimens each). Specimens were divided into 5 groups of 10 samples each and immersed in coffee, tea, coke, orange juice and distilled water for 30 days. Specimens were photographed with a digital camera (Fine Pix S9600). Color analysis was done with CS Photoshop software (CIE lab color space) at baseline, after color change and after repolishing. Obtained results were analyzed using Three-way ANOVA and LSD test. Level of significance was set at P<0.05 .   Results: All specimens showed a significant color change in all solutions except for water ( D E>3.3). The greatest color change occurred in B2 Spectrum composite resin in coffee while the smallest color change was observed in A2 Point 4 specimens in water. Except for water and coke, the difference in color change between the two composite resins in all solutions was statistically significant. Color changes of B2 shade were significantly higher than those of A2. Significant improvementswere observed in color of specimens after their repolishing. However, color change of specimens in coffee and tea did not improve to the clinically acceptable level by repolishing .    Conclusion : Color change of composite restorations depends on the type and shade of composite resin as well as patient's nutritional habits .